2019
DOI: 10.18632/oncotarget.26567
|View full text |Cite|
|
Sign up to set email alerts
|

SETD2 loss sensitizes cells to PI3Kβ and AKT inhibition

Abstract: Upregulation of the PI3K pathway has been implicated in the initiation and progression of several types of cancer, including renal cell carcinoma (RCC). Although several targeted therapies have been developed for RCC, durable and complete responses are exceptional. Thus, advanced RCC remains a lethal disease, underscoring the need of robust biomarker-based strategies to treat RCC. We report a synthetic lethal interaction between inhibition of phosphatidylinositol 3-kinase beta (PI3Kβ) and loss of SETD2 methylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…For patients in MoS1 subtype, axitinib, GDC0941, and dimethyloxalylglycine are more likely to delay progression of ccRCC. PI3K‐AKT pathway was widely reported as a promising druggable target in SETD2‐deficient ccRCC [ 71 ], indicating the inhibitors of PI3K‐AKT pathway might be suitable for MoS1 and MoS2 subtypes for their high SETD2 mutations, and based on GDSC online website, we identified several drugs for MoS1 as well, such as AZD8186, AZD5653, and Alpelisib. Collectively, the results mentioned above suggested MoSs classifier might be a potential tool for developing individualized treatment strategies for different patients.…”
Section: Discussionmentioning
confidence: 99%
“…For patients in MoS1 subtype, axitinib, GDC0941, and dimethyloxalylglycine are more likely to delay progression of ccRCC. PI3K‐AKT pathway was widely reported as a promising druggable target in SETD2‐deficient ccRCC [ 71 ], indicating the inhibitors of PI3K‐AKT pathway might be suitable for MoS1 and MoS2 subtypes for their high SETD2 mutations, and based on GDSC online website, we identified several drugs for MoS1 as well, such as AZD8186, AZD5653, and Alpelisib. Collectively, the results mentioned above suggested MoSs classifier might be a potential tool for developing individualized treatment strategies for different patients.…”
Section: Discussionmentioning
confidence: 99%
“…Terzo et al also reported that there is a synthetic lethal interaction between SETD2-deficiency and PI3Kβ-AKT inhibition in kidney cancer [50]. The phosphoinositide 3-kinase (PI3K)-AKT axis is a very important signaling pathway in cell proliferation and it is frequently changed in cancers [51].…”
Section: Synthetic Lethality Between Epigenetic Alterations and Non-ementioning
confidence: 99%
“…SETD2 loss or inactivation has been associated with enhanced response to mTOR inhibition through alterations in oxidative metabolism and protein synthesis pathways. 73,74 Shared loss of NOTCH1 in both dogs also carries relevance to osteosarcoma, as the NOTCH signaling pathway plays an important role in osteogenic differentiation. 75 Dysregulation of this pathway is linked to occurrence and progression of defects involving this process.…”
Section: Discussionmentioning
confidence: 99%